Mercy for money: Torture’s link to profit in Sri Lanka, a retrospective review - Wendell Block, Block; Jessica Lee, Lee; Kera Vijayasingham (Torture)
Background: The purpose of this retrospective study is to describe the pattern of bribe taking in exchange for release from torture, during and after the decades-long war in Sri Lanka. Methods: We reviewed the charts of 98 refugee claimants from Sri Lanka referred to the Canadian Centre for Victims of Torture for medical assessments prior to their refugee hearings in Torontobetween 1989 and 2013. We tallied the number of incidents in which claimants described paying cash or jewelry to end torture, and collected other associated data such as demographics, organizations of the perpetrators, locations, and, if available, amounts paid. We included torture perpetrated by both governmental and nongovernmental militant groups. Collected data was coded and evaluated. Findings: We found that 78 of the 95 subjects (82.1%) whose reported ordeals met the United Nations Convention Against Torture/International Criminal Court definitions of torture described paying to end torture at least once. 43 subjects paid to end torture more than once. Multiple groups (governmental and non-governmental) practiced torture and extorted money by doing so. A middleman was described in 32 percent of the incidents. Payment amounts as reported were high compared to average Sri Lankan annual incomes. The practice of torture and related monetary extortion was still reported after the end of the war, inclusive of 2013. Interpretation: Torture in Sri Lanka is unlikely to end while profit motives remain unchallenged. As well as health injuries, victims of torture and their families suffer significant economic injuries while their assailants are enriched. The frequent link between torture and impunity means multiple populations the world over are vulnerable to this abuse.